2020
DOI: 10.1016/j.tcm.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective strategies to prevent breast cancer therapy-induced cardiotoxicity

Abstract: Breast cancer is the most common malignancy affecting females, with over 260,000 new cases annually and over 3.1 million survivors in the United States alone. Exposure to potentially cardiotoxic therapies, including anthracyclines, trastuzumab, and radiation therapy, coupled with host factors, place patients at increased risk for the development of cardiovascular disease (CVD) compared to non-cancer controls. Overall survival outcomes are significantly worse in patients who develop CVD, and in certain breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 42 publications
(49 reference statements)
0
60
0
11
Order By: Relevance
“…In addition, dexrazoxane could also be a reason why there was no significant increase in the incidence of cardiotoxicity in the over-dose group in this study. Although dexrazoxane does not completely eliminate doxorubicin cardiotoxicity [ 21 , 25 ], it is still an option for primary prevention to reduce the risk of doxorubicin cardiotoxicity [ 7 , 25 ]. Published data have shown that patients with sarcoma can receive a mean cumulative doxorubicin dose of 600-750 mg/m 2 without a significant increase in cardiotoxicity when they are administered dexrazoxane [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dexrazoxane could also be a reason why there was no significant increase in the incidence of cardiotoxicity in the over-dose group in this study. Although dexrazoxane does not completely eliminate doxorubicin cardiotoxicity [ 21 , 25 ], it is still an option for primary prevention to reduce the risk of doxorubicin cardiotoxicity [ 7 , 25 ]. Published data have shown that patients with sarcoma can receive a mean cumulative doxorubicin dose of 600-750 mg/m 2 without a significant increase in cardiotoxicity when they are administered dexrazoxane [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS serves a main driver in drug-induced cardiotoxicity, and thereby many antioxidants have undergone preclinical development or clinically research for cardiotoxicity. For example, dexrazoxane, an iron chelating agent against iron-mediated oxidative stress, is the cardio-protective medicine approved by FDA in July 1995 for preventing anthracycline-induced cardiotoxicity, and now has been widely applied in the clinical practice (Padegimas et al, 2020). In addition, numerous natural antioxidants serve as adjuvant therapies to reduce drug-induced cardiotoxicity, such as berberine, epigallocatechin-3-gallate, and resveratrol (Coelho et al, 2017;Yu et al, 2018).…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…PEGylated liposomal formulations of DOX can reduce the incidence of cardiotoxicity, though they have been associated with other side effects such as skin toxicity [15]. Currently, there are no cardiotoxicity-specific treatments, neither prophylactic nor curative, and cardioprotective drugs trialled in patients to treat DOX cardiotoxicity are sparse and include standard heart failure medications such as renin angiotensin system blockers and beta blockers [12,16]. Therefore, there is an unmet clinical need for more targeted cardioprotective therapy for cancer survivors with DOX cardiotoxicity, or, even more importantly, prophylactic treatment for cancer patients receiving DOX to minimise the incidence of cardiotoxic side effects leading to heart failure.…”
Section: Introductionmentioning
confidence: 99%